2019
DOI: 10.1186/s13063-018-3114-5
|View full text |Cite
|
Sign up to set email alerts
|

Preventing falls among older fallers: study protocol for a two-phase pilot study of the multicomponent LIVE LiFE program

Abstract: BackgroundFalls reflect sentinel events in older adults, with significant negative consequences. Although fall risk factors have been identified as intrinsic (e.g., muscle weakness, balance problems) and extrinsic (e.g., home hazards), most prevention programs target only intrinsic factors. We present the rationale and design of a home-based multicomponent fall prevention program—the LIVE LiFE program—for community-living older adults. The program adapts and expands the successful Lifestyle Intervention Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
0
12
0
4
Order By: Relevance
“…Another study in Iran reported that a multicomponent program including environmental modifications and exercise programs resulted in a significant decrease in falls prevalence among older adults living in nursing homes. 21 ) In a systematic review, Granbom et al 29 ) showed that multicomponent programs are more effective than single-component programs for fall prevention. They also suggested that interventions should integrate the exercise program into daily life and make the home environment safer as the place of residence for older adults to allow older adults to be more likely to continue the exercise program and stay active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in Iran reported that a multicomponent program including environmental modifications and exercise programs resulted in a significant decrease in falls prevalence among older adults living in nursing homes. 21 ) In a systematic review, Granbom et al 29 ) showed that multicomponent programs are more effective than single-component programs for fall prevention. They also suggested that interventions should integrate the exercise program into daily life and make the home environment safer as the place of residence for older adults to allow older adults to be more likely to continue the exercise program and stay active.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the interventions in fall prevention programs in older people include exercise, use of medication, life environment interventions, use of support technologies such as alarms next to the bed, social environment interventions like training caregivers of older adults, and changes in the organizational system. 19 - 21 , 29 ) However, the effects of fall prevention programs on fall risk in older people differ in the literature. For example, a meta-analysis by Vlaeyen et al 30 ) showed that single-component interventions to prevent falls did not affect the number and risk of falls in more than half of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has also been integrated into some current Swedish guidance, on physical training, balance and more, issued from the National Board on Health and Welfare in the form of training for professionals working with older people and fall prevention [ 116 ]. However, effectiveness of exercise-based interventions is dependent on the uptake and long-term adherence [ 117 ]. Groups sessions led by professionals over a longer period (1 year or more) seems to affect this aspect positively but can be costly, foremost in terms of human resources needed if provided to a large population of older people.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility of a multicomponent LiFE format was demonstrated by Granbom et al (2019). The multicomponent LIVE LiFE format improved all performance measures with small to large effect sizes, showing significant differences between the intervention and control group (Granbom et al, 2019).…”
Section: Current Evidence Regarding Feasibility and Effectivenessmentioning
confidence: 95%